Engineering Purse Line Hauler Machine For Hydraulic Axle Capstan On Mini Purse Seine Boat - Soepardi, Sugiono; Istrianto, Kadi; Fanani, M. Zainal; Samu, Markus Samu; Suharyanto, Suharyanto; Perangin-angin, Robet (Politeknik Kelautan dan Perikanan Karawang, 2023)
Purse seine or purse seine is one of the dominant fishing tools for catching pelagic (surface) fish which operates by circling schools (schooling) of fish. In the process of circling a school of fish, the bottom must be crimped immediately and quickly using a crimping rope or what is usually called a